Pengembangan Permainan Edukatif Pahlawan Nasional Berbasis Android - Andhi Setiawan; Rinta Kridalukmana; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
With over time the smartphone is increasingly recognized by the public, it is contrary to the interest in learning about the history of Indonesia, especially the National Hero. Because of it, the idea to combine these two, which combines the sophistication of a smartphone with a history of national hero. Lack of instructional media on a national hero also be one of the factors that led to the creation of this application, not only can be an alternative medium of learning from the lessons of history, this application can also be one of the games that can entertain users. This application intended to provide additional knowledge about the national hero aside from the lessons taught in schools or other educational institutions, the media smartphone is well known by the public is expected that these applications can easily be accepted and may be useful for users who play this application.